Intestinal obstruction due to annular pancreas in neonatal period: a case report - Florian, Luis S. (2022)
Annular pancreas is a rare congenital malformation characterized by a pancreatic ring surrounding the descending part of the duodenum. It occurs in 1:20,000 live births. The age of presentation depends on the severity of the intestinal obstruction. The diagnosis requires imaging studies and surgical exploration. This is the case of a 13-day-old newborn admitted to the Neonatal Intensive Care Unit of Hospital Nacional Arzobispo Loayza. He presented with gastric residuum, vomiting and intermittent abdominal distension. Given the persistent gastrointestinal symptoms despite the treatment administered, a radiological examination of the upper digestive tract with contrast dye was conducted. Signs of duodenal stenosis were found. An exploratory laparotomy showed a postoperative diagnosis of annular pancreas. Kimura’s diamond-shaped side-to-side duodenoduodenal anastomosis was performed as a definitive treatment.